Baltijas Psiholoģijas Žurnāls; 1. sēj., Nr.1 - Latvijas Universitāte. Psiholoģijas nodaļa; Miezīte, Solveiga; Raščevska, Malgožata (Latvijas Universitāte. Psiholoģijas nodaļa, 2000)
Saturs / Contents Editorial 3 Groups and Workshops in Interethnic Conflict Resolution: Their Accomplishment and Promise, With Special Reference to the Baltic Context / Juris G. Draguns 4 Psychopathology of Altered States of Consciousness / Imants Baruss 12 Dissociation, Hostility, Resentment and Intolerance in Relation to Familial and Political Abuse / Sandra Sebre 27 Development of an Academic Base for Public Health Research and Practice in Latvia / Ilze Kalnins and leva Ranka 46 An Exploratory Study of the Structure-of-Intellect and Creativity in Four and Five Year Old Children / Solveiga Miezitis 57 International Guidelines to Assist in Adapting Tests / Thomas Oakland 68 Motivation for Learning a Foreign Language: What Recent Research Has to Tell Us / Robert Burden and Marion Williams 77 Notes on Authors 82
Journal of Baltic Psychology
Baltic Journal of Psychology
No 2002. gada žurnāls tiek izdots ar nosaukumu "Baltic Journal of Psychology"
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology; Psiholoģija; Sociālā psiholoģija; Psihopatoloģija; Etnopsiholoģija; Bērnu psiholoģija; Izglītiības psiholoģija; Social psychology; Psychopathology; Child psychology; Educational psychology; Human interaction